2020
DOI: 10.3390/ph13050104
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Amb4269951, a Choline Transporter-Like Protein 1 Inhibitor, in Human Glioma Cells

Abstract: Choline transporter-like protein 1 (CTL1) is highly expressed in glioma cells, and inhibition of CTL1 function induces apoptotic cell death. Therefore, CTL1 is a potential target molecule for glioma therapy. Here, we investigated the therapeutic mechanism underlying the antitumor effects of Amb4269951, a recently discovered novel CTL1 inhibitor, in the human glioma cell line U251MG, and evaluated its in vivo effects in a mouse xenograft model. Amb4269951 inhibited choline uptake and cell viability and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…The inhibitory effect of Amb4269951 and Amb4269675 on cell viability was enhanced in a treatment-time-dependent manner. Time-dependent suppression of cell viability by Amb4269951 was also observed in U251MG glioma cells [20]. These effects of both compounds may be due to the inhibition of choline uptake, which inhibits choline metabolic systems, including the Kennedy pathway, and thus suppresses phospholipid synthesis in the cell membrane.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The inhibitory effect of Amb4269951 and Amb4269675 on cell viability was enhanced in a treatment-time-dependent manner. Time-dependent suppression of cell viability by Amb4269951 was also observed in U251MG glioma cells [20]. These effects of both compounds may be due to the inhibition of choline uptake, which inhibits choline metabolic systems, including the Kennedy pathway, and thus suppresses phospholipid synthesis in the cell membrane.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, we discovered isoquinoline derivative Amb4269951 and its derivative, Amb4269675, from a library of plant-derived natural organic compounds during the search for compounds that inhibit both CTL1-mediated choline uptake and cell viability in MIA PaCa-2 cells [19]. We reported that Amb4269951 causes apoptosis-induced cell death in human glioma cells by suppressing the expression of apoptosis inhibitor survivin through the production of ceramide caused by CTL1-mediated inhibition of choline uptake [20]. However, neither Amb4269951 nor Amb4269675 have been studied in pancreatic-cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations